The next big thing in learning and behavioral disabilities - Cook, Bryan G.; Tankersley, Melody; Landrum, Timothy J. (Emerald Publishing Limited, 2021)
Responding to the need for educational stakeholders to be equipped to plan for constantly evolving developments in policy and practice for learners with learning and behavioral disabilities, this edited collection collates contributions from authors who predict what the next big things in the field will be, and offer recommendations on how to prepare for the future they envision. The chapters cover a broad range of topics that include developments related to students' legal rights and services, how research is utilized by practitioners, using practice-based evidence to promote the use of evidence-base practices, open science, neuroscience and special education, professional development for teachers, adaptive tier-2 interventions, the field of emotional and behavioral disorders, reading and students with autism spectrum disorder, and innovations in early writing. Chronicling, too, the concerns and cautions that the authors have about what they see as the next big thing, this collection is a compelling resource for anyone looking to the future of the field, and thinking about how they can be at the front of developments in order to navigate change in a way that generates positive effects.
Includes index.
Keywords: Learning disabled children -- Education.; Developmentally disabled children -- Education.; Education -- Special Education -- Learning Disabilities.; elektronické knihy; electronic books